(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Tuberculosis (TB) remains a major global health concern, particularly among vulnerable populations such as children. In recent decades, migration has emerged as a significant factor influencing the epidemiology of TB. This review examines the relationship between migration processes and the spread of tuberculosis in children, focusing on biological, social, and healthcare-related determinants. Migrant children are exposed to multiple risk factors, including overcrowding, malnutrition, interrupted vaccination, and limited access to healthcare services, all of which contribute to increased susceptibility to TB infection and progression to active disease. Additionally, migration disrupts continuity of care and contributes to delayed diagnosis and treatment interruption, thereby facilitating ongoing transmission and the emergence of drug-resistant tuberculosis. The review highlights the importance of integrated public health strategies, including early screening, vaccination coverage, improved living conditions, and cross-border healthcare coordination. Addressing migration-related determinants is essential for reducing the burden of pediatric tuberculosis and achieving global TB control goals.